The Implementation of the Green Economy in Indonesia and the Impacts on Human Rights - Faiza Danishyar (Fakultas Hukum Universitas Islam Indonesia, 2026)
This study analyzes the implementation of the green economy in Indonesia and its impact on human rights through a normative juridical and descriptive-analytical approach. Drawing on key policies such as Law No. 32 of 2009, Presidential Regulation No. 98 of 2021, and the Paris Agreement, it examines how environmental sustainability aligns with social inclusion and justice. Using the Human Rights-Based Approach (HRBA) and Environmental Justice Theory, the study finds that Indonesia’s initiatives—like the Low Carbon Development Initiative (LCDI) and the Green Growth Program—have advanced the rights to health, work, and a clean environment. However, challenges remain, including inequality, job loss in fossil fuel sectors, and limited participation of indigenous groups. The paper concludes that integrating human rights principles is essential for ensuring an inclusive and equitable green transition